Disability Studies and Inclusive Design: Advancing Accessible Environments, Technologies, and Societal Attitudes - Syarifuddin; Gamar Al Haddar (West Science Social and Humanities Studies, 2023)
This research delves into the intersection of Disability Studies and Inclusive Design within Indonesia, focusing on advancing accessible environments, technologies, and community attitudes. Through a mixed-methods approach comprising qualitative interviews and quantitative surveys, the study unveils insights into the prevailing state of disability inclusion. The findings illuminate disparities in accessible environments across urban and rural regions, showcase varying levels of technology integration, and provide a nuanced understanding of community attitudes. The research underscores the imperative of policy interventions, awareness campaigns, and collaborative efforts to foster an inclusive Indonesian society.